Increased levels of peptidylarginine deiminase 2 in synovial fluid from anti-CCP-positive rheumatoid arthritis patients: Association with disease activity and inflammatory markers - Damgaard, Dres; Senolt, Ladislav; Nielsen, Claus H (Rheumatology (Oxford, England), 2016)
OBJECTIVE: To quantify peptidylarginine deiminase 2 (PAD2) in SF of RA patients and OA patients, and to determine the association between PAD2 levels, disease activity and inflammatory markers in RA. METHODS: Blood and SF samples were obtained from 39 RA patients and 40 patients with OA. PAD2 content and PAD activity were measured by means of in-house assays. TNF-α, IL-1β, IL-6, IL-8, IL-10 and IL-12 were measured using flow cytometry. RESULTS: PAD2 levels and PAD activity were higher in SF from RA than OA patients (P < 0.0001 and P = 0.03, respectively), as were all cytokine levels (P < 0.0001-0.05). SF PAD2 levels were higher among anti-CCP-positive patients than among anti-CCP-negative patients (P = 0.005). PAD2 levels in SF from RA patients correlated with disease activity, as assessed by DAS28 (P < 0.005). Moreover, SF PAD2 levels correlated with circulating CRP and anti-CCP levels (P < 0.0006), as well as with leucocyte count, IL-6, IL-8 and IL-10 levels in SF (P < 0.0001-0.02). PAD activity in SF was higher in RA patients than in OA patients, and correlated with PAD2 concentration. CONCLUSION: Extracellular PAD2 levels in SF correlate with disease activity in RA patients. Anti-CCP-positive RA patients have higher PAD2 levels in SF than anti-CCP-negative RA patients and OA patients. Since we could demonstrate enzymatically active PADs in SF, we propose that free, extracellular PAD is of pathogenic relevance.
Keywords: dospělí; Enzyme-Linked Immunosorbent Assay; peptidylarginine deiminase; Arthritis, Rheumatoid; osteoartróza; Female; Cytokines; revmatoidní artritida; biologické markery; C-Reactive Protein; Biomarkers; Adult; ženské pohlaví; citrullination; cytokiny; počet leukocytů; lidé; Inflammation Mediators; synoviální tekutina; peptidylarginindeiminasa typu 2; Humans; peptidylarginindeiminasy; Leukocyte Count; ELISA; Male; cyklické peptidy; Aged; Autoantibodies; Hydrolases; rheumatoid arthritis; Protein-Arginine Deiminase Type 2; cytokines; Osteoarthritis; Peptides, Cyclic; Synovial Fluid; mediátory zánětu; C-reaktivní protein; lidé středního věku; senioři; mužské pohlaví; hydrolasy; Protein-Arginine Deiminases; Middle Aged; autoprotilátky